DYNAMIC ANALYSIS OF CAR BODY STRUCTURE LOCOMOTIVE DH - HAMZAH SURYONO (NIM : 13107064); Dosen Pembimbing : Rachman Setiawan, ST, M.Sc.,Ph.D., AMAR
The locomotive is used as the prime mover in a railway vehicle. As a case study from this assignment, PT INKA as the one and only railway manufacturing company in Indonesia is willing to produce diesel hydraulic locomotive for the first time in Indonesia. Due to the production of a new locomotive is the first time made, it would require engineering analysis process in the stage production of locomotives to produce products with good quality. Engineering aspects that must be done in the analysis of one of them is the dynamic analysis of the structure of the locomotive body. Dynamic analysis includes modal analysis structure and harmonic analysis is performed based on finite element theory. The first step performed modal analysis on the structure of the locomotive using the software ANSYSTM. Modal analysis is needed to determine the natural frequencies and modes of vibration of the structure for each natural frequency. Harmonic analysis is then performed to obtain FRF response curve of the structure due to harmonic excitation input from the outside. The next step after a dynamic analysis is done, then to verify the results with some experimental data such as results of vibration data on the actual structure. Verification is done by comparing the natural frequency of the first bending vibration mode. Additionally, verification of the frequency components of the locomotive which is expected no component that works on the natural frequencies of structure, so the potential occurrence of resonance vibrations can be avoided. From the overall analysis, obtained a decision to make modifications to the structure. This is because there are modes of vibration with a critical natural frequency of 10.042 Hz, 11.391 Hz, and 26.603 Hz which is almost similar to the operational frequency. To keep the frequency of modifications is done by adding the stiffness of the structure by increasing the thickness of the plate on the structure so it has a natural frequency value is increased to 10,148 Hz, 11,411 Hz, and 26,613 Hz. After the modified structure, harmonic analysis was then performed to determine stress that occurs due to dynamic loading vibration of critical from engine and vibration of bogie. Stress that occurs due to dynamic loading is 100 MPa and 49.9 MPa in the vicinity od mounting engine / in the midle of the structure.